Price and Purchase Decisions for Thrift Product: The Mediating Role of Brand Image - Isalman Isalman (Telaah Bisnis, 2026)
This study examines the effect of Price on Purchase Decisions, mediated by Brand Image, among university students purchasing thrift fashion products in Kendari City. The novelty of this study lies in explaining the psychological mechanism through which Brand Image translates price perceptions into purchase decisions within the underexplored context of thrift fashion. Using a quantitative explanatory approach, data were collected from 200 respondents through purposive sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results show that Price positively and significantly affects Brand Image and Purchase Decisions, and that Brand Image, in turn, positively influences Purchase Decisions and significantly mediates the relationship between Price and Purchase Decisions. Theoretically, this study extends Signaling Theory and consumer behavior literature by demonstrating the mediating role of Brand Image in second-hand fashion consumption. In practice, the findings suggest that thrift businesses should adopt pricing strategies that reinforce their brand image to influence consumer purchase decisions and promote sustainable fashion consumption.